Microclimate and development of 'Conilon' coffee intercropped with rubber trees - Partelli, Fábio Luiz; Araújo, André Vasconcellos; Vieira, Henrique Duarte; Dias, Jairo Rafael Machado; Menezes, Luis Fernando Tavares de; Ramalho, José Cochicho (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the influence of intercropping 'Conilon' coffee (Coffea canephora) with rubber trees on coffee tree microclimate, nutrition, growth, and yield. Rubber trees were planted in two double rows 33 m apart, with 4x2.3 m spacing between plants. Treatments consisted of the distances from the coffee plants to the rubber trees: 3, 6, 9, 12, and 15 m. Measurements of atmospheric variables (temperature, irradiance, and relative humidity), leaf nutrient concentration, internode length of plagiotropic and orthotropic branches, individual leaf area, chlorophyll content, and yield were performed. Intercropping promotes changes in the microclimatic conditions of coffee plants close to rubber trees, with reduction of temperature and irradiance level and increase in air relative humidity. The proximity of the coffee tree to the rubber trees promotes the elongation of the plagiotropic and orthotropic branches and increases the individual leaf area; however, it does not affect leaf concentrations of N, K, Mg, Fe, Zn, and B in 'Conilon' coffee and does not have a negative impact on yield.
Keywords: Coffea canephora; Hevea brasiliensis; irradiance; monoculture; shading